Potential of silvopastoral systems in the rain forests - Toledo, José M.; Torres, F (International Center for Tropical Agriculture, 1989)
Grazing animals, mainly cattle and sheep are important components of the agricultural production systems in the rain forest areas. Dwarf sheep and goat are common in the humid zone of Africa, as a source of meat and income. Carabao (water buffaloe) and cattle are the main draft force in crop (mainly rice) production systems in Southeast Asia, where grazing under plantations for beef production is also common. Given the high cattle population and high levels of demand for beef and milk in tropical America, ranching for cattle production in the humid tropics has been expanding in the Brazilian Amazon and in Central America. Also small farmers after clearing the forest for crop production move into mixed farming systems incorporating cattle as a way of saving and income generation. The main problem of cattle ranching and mixed farming in the rain forest areas is the lack of sustainability of the production systems. Open pastures with the existing technology rapidly degrade increasing pressure for further deforestation. The paper discusses the possibilities and potential of integrated (tree-pasture) systems in the rain forests as means of developing sustainable production systems. Examples of spontaneous low stocking silvopastoral (grazed tree plantations) systems occurring in Southeast Asia as well as experiences with multipurpose trees (fence-shade-crop-fodder) in tropical America are presented. Research results on the interaction between trees and pastures, trees and grazing animals in silvopastoral systems, and about the shade tolerance of grasses and legumes, are presented. The socioeconomic and biological constraints for the development of integrated silvopastoral systems are discussed. Finally, suggestions for future research are presented.